Recydywa penologiczna w Republice Słowackiej i krajach europejskich - Griger, Jozef; Jasiński, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The authors are focused on the grasping the importance of correct recidivism as a background for adopting systemic measures in the criminal policy of the state. It also raises issues of deﬁning and estimating penitentiary recidivism, which is understood diﬀerently depending on the country, legal system and social and criminal conditions.
Keywords: polityka kryminalna; polityka oparta na dowodach; recydywa; kara pozbawienia wolności